Modelling and simulation of PWM switched autotransformer for voltage SAG mitigation using MATLAB/SIMULINK - Ahmad, Ismail (2015)
For some decades, power quality did not cause any problem, because it had no effect on most of the loads connected to the electric distribution system. When an induction motor is subjected to voltage sag, the motor still operates but with a lower output until the sag ends. With the increased use of sophisticated electronics, high efficiency variable speed drive, and power electronic controller, power quality has become an increasing concern to utilities and customers. Voltage sags is the most common type of power quality disturbance in the distribution system. It can be caused by fault in the electrical network or by the starting of a large induction motor. Although the electric utilities have made a substantial amount of investment to improve the reliability of the network, they cannot control the external factor that causes the fault, such as lightning or accumulation of salt at a transmission tower located near to sea. Custom power device like Dynamic voltage restorer and STATCOM are normally employed as a solution for mitigation of voltage sag. This project presents modelling and analysis of PWM switched autotransformer as a mitigating device for voltage sag disturbances. The proposed system has less number of switching devices and has good compensating capability in comparison to commonly used compensators. Simulation analysis of three-phase compensator is perfomed in MATLAB/SIMULINK software. Simulation results are presented for various conditions of faults and also the comparison result with and without of the PWM switched autotransformer.